ANALISIS KINERJA MESIN AMG CNC PLATE CUTTING MENGGUNAKAN METODE OEE (OVERALL EQUIPMENT EFFECTIVENESS) - Dwika Daffa Ashari; Viktor Naubnome; Najmudin Fauji (ROTOR, 2022)
In the industrial world, technology is an important thing that can help improve the quality of the industry. Every company that uses technology definitely needs an adequate maintenance system for tools and machines. The purpose of maintenance is to prevent unexpected machine breakdowns that can result in the production process stopping, endangering worker safety and increasing machine repair costs. One of the machines that are often used in the production process at PT XYZ is the AMG CNC plate cutting machine. Therefore, one method to determine the effectiveness of a cutting machine is Overall Equipment Effectiveness (OEE). Overall Equipment Effectiveness is a measurement made on performance related to the availability of process productivity and quality. As a result, by applying the OEE (Overall Equipment Effectiveness) method for performance analysis of the AMG CNC plate cutting machine, we can find out the value for availability of 91%, performance efficiency of 96%, and rate of quality product of 99%, the measurement results of the AMG CNC plate machine cutting in January 2021 using the OEE method of 86% which has passed the value of the OEE world standard of 85%. the value of the six big losses obtained is the breakdown loss value of 1.8%, the set up and adjustment value of 10%, the idle and minor stoppage value of 3%, the value of reduce speed losses of 5.3%, the value of process defect losses of 1 ,1%, the value of reduce yield losses is 0.06%.